Corneal Manifestations of Inflammatory Bowel Disease. (17th November 2019) - Czompa, Levente; Barta, Zsolt; Ziad, Hassan; Nemeth, Gabor; Rentka, Aniko; Aszalos, Zsuzsa; Zold, Eva; Gesztelyi, Rudolf; Zsuga, Judit; Szodoray, Peter; Kemeny-Beke, Adam
ABSTRACT: Purpose : To evaluate detailed corneal parameters of inflammatory bowel disease (IBD) patients, including Crohn's disease (CD) and ulcerative colitis (UC) patients, and to assess associations between anterior segment values and other clinical variables. Methods : This prospective cross-sectional case-control study at a tertiary referral center included 30 CD patients, 36 UC patients and 80 age- and gender-matched controls with no ocular symptoms or ocular surface disorders. All study participants underwent a comprehensive ophthalmological evaluation with special interest in dry eye disease (DED). Corneal parameters were evaluated by Pentacam. Results : The mean age of CD patients, UC patients, and controls was 45.80 ± 11.55 years, 52.00 ± 16.05, and 50.68 ± 14.62, respectively. The average disease duration was 12.72 ± 5.83 years for CD patients and 15.94 ± 10.09 years for UC patients. All pachymetric (center, apex and thinnest) and corneal volume (CV) measurements were significantly decreased, while anterior chamber angle width (ACA) values were significantly increased on both sides in all IBD patients compared to those in controls ( p < .05). In addition, several anterior segment parameters were altered unilaterally in CD or UC patients. Negative correlations were found between corneal parameters and Schirmer I test values. Conclusions : Our investigations suggest that IBD patients have thinner corneas compared to that of controls. The coexistence of reduced tear quantity seems to have an additional impact on the thinning of the cornea in IBD patients. Early recognition of corneal impairments, a possible extraintestinal manifestation of IBD, should be included in the disease checkup to reduce vision-threatening developments.